Receiver Processing of the Multibeam Azimuth Scanning CC-OFDM-MIMO Radar - Devy Kuswidiastuti; L. P. Ligthart; Gamantyo Hendrantoro; Titiek Suryani; Prasetiyono Hari Mukti; Yuyu Wahyu (IEEE Access, 2025)
The proposed CC-OFDM-MIMO radar enables the development of software-defined radar by using array antennas to provide multiple high-resolution beams with low peak SLLs. The radar requires no RF phase shifters because the amplitude and phase control for multiple beamforming are provided directly from the waveform generation stage. The multiple beams are transmitted simultaneously and continuously without beams switching that makes the radar has full continuous observations over the wide coverage of −45 to 45 degree. The proposed design of long-range radar with low power transmission can be implemented by transmitting multi-orthogonal CC-OFDM symbols in series, which extends the maximum unambiguous range and improves the Signal-to-Noise of the radar system. The orthogonality of the beams and the symbols obtained by applying orthogonal Golay codes and sub-band frequency scheduling arrangements to avoid interference between beams and between symbols. In this paper, parallel receiver processing works by correlating the received signals with the multiple signal references that are well-known by the transmitters and receivers. The output of the multibeam correlators gives the first estimation of the target profiles in terms of the targets range and its direction. The target direction can be verified furthermore by correlating the spectrum of the received echo signal after delay compensation with the Golay codes which corresponds to a specific beam and specific symbol. With the orthogonal nature of Golay Codes, the receiver can distinguish targets which come from different beams, even though the beams are using the same frequency band. After the target is detected within a specific beam, and at a certain range, Doppler processing can be done by observing the phase variation between the samples of the received signal and the signal references. The coherence processing for Doppler detection can be done over one period of symbol, and the Doppler resolution can be improved by coherence processing over one frame period consisting of 12 orthogonal symbols. Simulation of the receiver processing is done for two targets located in the same beam, in neighboring beams and in co-channel beams. The results show that the radar could distinguish two targets with 60 meters in separation with SLLs as low as -80dB. Additionally, the radar is able to detect moving targets with better resolution because the velocity can be obtained from the phase variation over one symbol duration and over the whole symbol series.